Key Indicators for a Countercyclical Capital Buffer in Norway - Trends and Uncertainty - Karsten R. Gerdrup; Aslak Bakke Kvinlog; Eric Schaanning (Norges Bank, 2013)
The credit-to-GDP gap has a prominent role in the Basel Committee's frame- work for a countercyclical capital buffer under Basel III. The Committee uses a one-sided Hodrick-Prescott filter to calculate the trend of credit-to-GDP. In this paper we suggest applying the filter to a sample of the indicator where the historical observations have been augmented with forecasts of the indicator. This may provide a more robust estimate of the gap (deviation of indicator from its trend) and thereby a more reliable early warning of a crisis. We analyse Norges Bank's four key indicators for identifying a build-up of imbalances: credit-to-GDP, house prices-to-income, real commercial property prices and the wholesale funding ratio of Norwegian credit institutions. We find that we can reduce revisions in the gaps and improve their signalling quality as indicated by a ROC/AUC analysis even by using forecasts based on a relatively simple method. The forecast is an average of the quarterly indicator variables over the last 4 quarters and the forecast horizon is 5 years.
hdl:11250/2506995
Keywords: 330; AUC; ROC; countercyclical capital buffer; filters; macroprudential policy